Analysis of MSME Competitiveness in Denpasar During the COVID-19 Pandemic - I Gusti Ayu Agung Virna Pryanka; Ni Putu Wiwin Setyari (Integrated Journal of Business and Economics (IJBE), 2022)
Micro, Small and Medium Enterprises (MSMEs) in Denpasar are important assets to strengthen the foundation of the regional economy. The MSME sector is currently one of the government's focuses being sought to quickly rise from the downturn due to the COVID-19 pandemic, which has a huge impact on all sectors of economy. Thus, MSMEs are expected to be able being highly competitive to encourage economic growth and people's income. The purpose of this research is to analyze the correlation between the variables of resource availability, business capability, and business performance that affect the competitiveness of MSMEs in Denpasar during the COVID-19 pandemic.This research analyze in Denpasar with a sample of 100 MSME units using the Accidental Sampling method. Data was collected using a survey approach through questionnaires and in-depth interviews. The rearch was conducted using Confirmatory Factor Analysis (CFA), to testing the suitability of the data in the field with the model formed using AMOS 21.The results showed that the three variables are interrelated with significant positive values and had an effect on the competitiveness of SMEs. Indicators on the factor of resource availability have the strongest influence on the competitiveness of MSMEs in Denpasar during the COVID-19 pandemic.